(untitled) (Journal of Economic Research & Business Administration, 2018)
The education system is an essential component of the socio-economic system of the state, which has an impact on all aspects of its activities. The influence of education on economic growth is proved by leading Russian, domestic and foreign economists. The implemented reform in the sphere of higher education is aimed at the simultaneous solution of a number of problems: first of all, to improve the quality of education and training of personnel, integration into the international educational space, structurallysubstantial academic design is adequate to the needs of society, the state, employers, the individual. Higher education and the science system are subject to radical changes in the world closely related to the implementation of the idea of a knowledge-based economy. Funding plays a very important role here, in fact its function and effect. The level of expenditures and the way of their distribution is today about the potential of a given country. In the most developed economies, the financing of higher education and science is closely related to the efficiency, needs of the enterprise sector and is a derivative of healthy competition. This article is devoted to the problems of financing the education and science systems in Kazakhstan in conditions of the formation of a knowledge-based economy. The main stages of budgetary and extra-budgetary financing of educational institutions are considered. Studied models of normative financing of education, features, problems and consequences of their implementation. The article is intended for specialists in the field of economics, management and financing of the education and science system.